2017
DOI: 10.20463/jenb.2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

Development of an anaerobic threshold (HRLT, HRVT) estimation equation using the heart rate threshold (HRT) during the treadmill incremental exercise test

Abstract: [Purpose]The purpose of this study was to develop a regression model to estimate the heart rate at the lactate threshold (HRLT) and the heart rate at the ventilatory threshold (HRVT) using the heart rate threshold (HRT), and to test the validity of the regression model.[Methods]We performed a graded exercise test with a treadmill in 220 normal individuals (men: 112, women: 108) aged 20–59 years. HRT, HRLT, and HRVT were measured in all subjects. A regression model was developed to estimate HRLT and HRVT using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Among typical methods of determining AT are the lactate threshold (LT), which is based on blood lactate levels, and ventilator threshold (VT), which is measured by respiratory gas. 9 The LT and VT do not typically appear at the same time, and the LT generally tends to appear before the VT. In addition, the LT indicates a point of rapid change in blood lactate levels, and is considered an efficient and practical method with less subjective bias for determining an AT compared with the VT. 9,10 Weight loss through aerobic exercise results in reduced blood cholesterol, improved hypertension, increased insulin sensitivity, reduced risk of cardiovascular disease, and improved aerobic exercise capacity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among typical methods of determining AT are the lactate threshold (LT), which is based on blood lactate levels, and ventilator threshold (VT), which is measured by respiratory gas. 9 The LT and VT do not typically appear at the same time, and the LT generally tends to appear before the VT. In addition, the LT indicates a point of rapid change in blood lactate levels, and is considered an efficient and practical method with less subjective bias for determining an AT compared with the VT. 9,10 Weight loss through aerobic exercise results in reduced blood cholesterol, improved hypertension, increased insulin sensitivity, reduced risk of cardiovascular disease, and improved aerobic exercise capacity.…”
mentioning
confidence: 99%
“…9 The LT and VT do not typically appear at the same time, and the LT generally tends to appear before the VT. In addition, the LT indicates a point of rapid change in blood lactate levels, and is considered an efficient and practical method with less subjective bias for determining an AT compared with the VT. 9,10 Weight loss through aerobic exercise results in reduced blood cholesterol, improved hypertension, increased insulin sensitivity, reduced risk of cardiovascular disease, and improved aerobic exercise capacity. 11,12 Aerobic exercise also has reduced levels of leptin, insulin, cortisol, and thyroid stimulating hormone during submaximal exercise, [13][14][15] and it increases the activity of the vagus nerve, reduces resting heart rate, activates the parasympathetic nervous system (PNS), and provides for autonomic control.…”
mentioning
confidence: 99%
“…We divided the subjects of both genders according to a 7 : 3 ratio using Bernoulli's trials. We developed the regression model by using 70% of the subjects, and we used the remaining 30% of the subjects for cross-validation [30,31]. The actual sample size distribution according to Bernoulli's trials is shown in Table 2.…”
Section: Subjectsmentioning
confidence: 99%
“…This protocol's initial starting speed was 3.6 km/h and increased by 1.2 km/h every 2 minutes. The slope was at 0% at all stages [31]. We measured respiratory gas and heart rate continuously during the maximal exercise testing.…”
Section: Graded Exercise Test Using Treadmillmentioning
confidence: 99%
“…Therefore, Menzel & Hilberg 11 recommend using the anaerobic threshold (AT) intensity of each individual as the appropriate exercise intensity for weight loss. There are two representative methods of determining AT: lactate threshold using blood lactate levels (LT) and ventilatory threshold (VT) using respiratory gas 12 . LT, rather than VT, is more efficient in the determination of AT because it is a point of rapid change in blood lactate concentration, is less subjective in judgment, and more practical 13 .…”
Section: Introductionmentioning
confidence: 99%